The National Museum : Highlights : Art from 1945 to the Present. - Eckhoff, Audun; van der Ley, Sabrina; National Museum, Oslo (Oslo : Nasjonalmuseet for kunst, arkitektur og design, 2015)
Abramovic, Marina ; Adéagbo, Georges ; Advocaat, Gunnvor ; Allora & Calzadilla ; Alveng, Dag ; Aurdal, Synnove Anker ; Baird, Vanessa ; Baldessari, John ; Balka, Miroslaw ; Barclay, Per ; Becher, Bernd & Hilla ; Bergman, Anna-Eva ; Berntsen, Sofie ; Bjorgeengen, Kjell ; Bjorlo, Per Inge ; Bleken, Hakon ; Blume, Anna & Bernhard ; Bock, John ; Boltanski, Christian ; Book & Hedén ; Borchgrevink, Hanne ; Bourgeois, Louise ; Bratteli, Marianne ; etc.
Showcasing the great diversity to be found in comtemporary art, both in Norway and abroad, this catalogue presents 150 highlights from the National Museum's collection of art from 1945 to the present.
boek
Keywords: Noorwegen